Perbandingan Biaya Global Hemodialisis dan Dialisis Peritonal Pada Penyakit Ginjal Tahap Akhir: Tinjauan Sistematis Berdasarkan Tingkat Pendapatan Negara - Affifatu Annisa; Dwi Endarti; Auliya Abdurrohim Suwantika; Wening Wulandari (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The increasing prevalence of end-stage renal disease poses an economic challenge to healthcare systems worldwide. Hemodialysis and peritoneal dialysis are currently the most commonly used renal replacement therapy modalities, but their costs vary across components and economic contexts. This systematic review aims to compare the costs of hemodialysis and peritoneal dialysis across countries, considering income levels and economic perspectives. A systematic literature search was conducted using EBSCO, ProQuest, PubMed, Scopus, and SpringerLink databases, with studies conducted between 2015 and 2025. Studies reporting cost analyses of hemodialysis and/or peritoneal dialysis were included. The selection process followed PRISMA guidelines, and the methodology was assessed using the CHEERS 2022 checklist. A total of 33 studies were included for discussion across low- to high-income levels. Economically, peritoneal dialysis was found to be more cost-effective than hemodialysis in most of these studies. The difference in cost structure is attributed to direct medical costs, which constitute the largest component of costs. Hemodialysis treatment is more expensive due to the costs of dialysis machines, service facilities, labor, and infrastructure, as well as lost productivity and indirect medical costs. Advantages of peritoneal dialysis include lower transportation costs, reduced productivity loss, and accessibility to low- and middle-income countries. Several studies have also shown that peritoneal dialysis yields quality-adjusted life years (QALYs) comparable to hemodialysis. This systematic review concludes that peritoneal dialysis can be cost-effective in most high-income countries. It should be considered a treatment modality of choice to improve efficiency, control long-term costs, and support health insurance management.